GAMBARAN PROSES PENERIMAAN DIRI PADA INDIVIDU DEWASA AWAL YANG MERUPAKAN KORBAN PERCERAIAN - Massimiliano Di Matteo; Untung Subroto; Meike Kurniawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to describe the process of self-acceptance in early adult individuals who are victims of parental divorce. The research method used a qualitative approach with in-depth interviews with five participants aged 18-40 years. The results showed that the process of individual self-acceptance followed the stages of the Five Stages of Grief theory by Elisabeth Kübler-Ross, namely denial, anger, bargaining, depression, and acceptance. Each stage reflects different emotions and strategies in dealing with the psychological impact of parental divorce. The findings showed that social support from family, friends and the surrounding environment influenced the success of individuals in achieving self-acceptance. In addition, participants who are able to interpret the experience positively tend to be more easily reconciled with their condition. This study contributes to the development of self-acceptance theory in the context of early adult developmental psychology, as well as providing practical insights for psychologists, parents, and educational institutions in supporting individuals who experience parental divorce.